Secrecy Performance Analysis of Hybrid RF/VLC Dual-Hop Relaying Systems - Liu, Jiaoli; Wang, Jinyuan; Zhang, Bingyuan; Wang, Qinglin (Frontiers in Physics, 2021)
In this paper, the secrecy performance of a hybrid radio frequency (RF) / visible light communication (VLC) system is studied. In this hybrid system, the source node (i.e., Alice) transmits information to the relay node via the outdoor RF link. Nakagami-m fading and path loss are considered for the RF link. The relay node includes an outdoor component and an indoor component, which are connected by using a wired medium. The outdoor component receives and recovers information by using the decode-and-forward (DF) relaying scheme, and then transmits it to the indoor component. The indoor component then converts the received electrical signal into an optical signal by using a light-emitting diode. A legitimate receiver (i.e., Bob) deployed on the floor receives the optical signal. An eavesdropper (i.e., Eve) deployed in the RF or VLC link wiretaps the confidential information. In this paper, we use the secrecy outage probability (SOP) and the probability of strictly positive secrecy capacity (SPSC) to evaluate the system performance. We then obtain the closed-form expression for a lower bound on the SOP and an exact closed-form expression for the probability of SPSC when the RF and VLC links are wiretapped respectively. Numerical results are presented to validate the accuracy of our derivations. We further discuss the effects of noise standard deviation, equivalent threshold of the signal-to-noise ratio, and the floor radius on the system secrecy performance when the VLC link is eavesdropped. For the case when the RF link is eavesdropped, the impacts of the distance between Alice and the relay, path loss exponent, fading factor, and the distance between Alice and Eve on secrecy performance are also provided.